2023
DOI: 10.1021/acsbiomaterials.3c00307
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Mitochondria-Targeting Near-Infrared Fluorescent Probe for Viscosity, ONOO, Mitophagy, and Bioimaging

Abstract: Irregularities in mitochondrial viscosity and peroxynitrite (ONOO − ) concentration can lead to mitochondrial dysfunction. It is still a great challenge to develop near-infrared (NIR) fluorescent probes to simultaneously detect viscosity, endogenous ONOO − , and mitophagy. Herein, a multifunctional mitochondria-targeting NIR fluorescent probe P-1 was first synthesized for simultaneously detecting viscosity, ONOO − , and mitophagy. P-1 used quinoline cations as a mitochondrial targeting moiety, arylboronate as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…However, similar results of emission ∼460–535 nm for HAP nanoparticles synthesized through the chemical precipitation method were reported earlier by Machado et al Deshmukh et al reported similar fluorescence emission at a wavelength of 502 nm for HAP nanoparticles synthesized via a modified sol–gel route . These interesting results open up new arenas of application of fluorescent biomaterials as bioimaging probes for internal organs and tissues . In addition, the use of KNN attributes the composite to piezoelectric properties, which is the subject matter for the group’s ongoing research work.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, similar results of emission ∼460–535 nm for HAP nanoparticles synthesized through the chemical precipitation method were reported earlier by Machado et al Deshmukh et al reported similar fluorescence emission at a wavelength of 502 nm for HAP nanoparticles synthesized via a modified sol–gel route . These interesting results open up new arenas of application of fluorescent biomaterials as bioimaging probes for internal organs and tissues . In addition, the use of KNN attributes the composite to piezoelectric properties, which is the subject matter for the group’s ongoing research work.…”
Section: Discussionsupporting
confidence: 78%
“…56 These interesting results open up new arenas of application of fluorescent biomaterials as bioimaging probes for internal organs and tissues. 57 In addition, the use of KNN attributes the composite to piezoelectric properties, which is the subject matter for the group's ongoing research work. From an application perspective, such piezoactive composites would be useful for designing 3D-printed scaffolds in bone tissue engineering applications.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Previous studies have reported that the ionic carriers, monensin (Mon), nystatin (Nys), and lipopolysaccharides (LPS), disrupt ion homeostasis, leading to mitochondrial dysfunction and viscosity changes. 36–40 In addition, carbonyl cyano-chlorophenyl hydrazone (CCCP) can also cause changes in mitochondrial viscosity. 41 Therefore, to investigate the monitoring of intracellular mitochondrial viscosity changes by YPE , we used different drug stimuli to regulate changes in the mitochondrial microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…25 Both these derivatives utilize a C-12 alkyl chain that may help in anchoring the fluorophore to the mitochondrial matrix. Other derivatives that monitor autophagy apart from monitoring other processes as analyte detection or viscosity sensing include quinolinium containing P1, 26 MQA-P, 17 a benzo indole derivative (MN-V), 27 a styryl benzothiazole derivative 28 . Imaging of mitochondria and detection of ONOO − was also reported through a light-triggered process using a styrylnaphthalene scaffold (TPONOO-1).…”
Section: Introductionmentioning
confidence: 99%